Synthesis and Evaluation of Nanoparticles Formulations of Anti-Tubercular Drugs - Mahesh Kumar; Yogendra Singh; Arun Garg; Ashutosh Upadhyay; Girish Kumar; Prof (Dr) Tarun Virmani (International Journal of Medical Toxicology and Legal Medicine, 2024)
Aim: The purpose of this research was to prepare isoniazid loadedsolid lipid nanoparticles (SLNs) for oral administration aiming at improving the therapeutic efficiency in the treatment of tuberculosis. The isoniazid loaded SLNs were designed using glyceryldibehenateas a lipid component and tween 80 as surfactant by homogenization technique. Box-Behnken design was implemented to get optimized SLN formulation of isoniazid having lipid concentration, surfactant concentration, and homogenization speed as independent variables and particle size and entrapment efficiency as dependant variables. The Formulation having lipid concentration 100 mg, surfactant concentration 15 mg, and homogenization time of 15 minute was found optimized with particle size of 247.65 ± 1.2 nm and entrapment efficiency of 80.68 ± 3.2 %. The optimized formulation provided prolonged release of 89.94 ± 1.5% after 6 hours which was more than 90% within 1 hour for pure drug solution suggesting improved duration of action. These results suggested the improved therapeutic efficiency of SLN loaded with isoniazid which required pharmacokinetic and pharmacodynamic studies for further confirmation. The present study concluded that SLNs may be utilized to provide a more prolonged, enhanced release of the drugs without altering the dosage.